Cognitive, Linguistic, and Motor Abilities in a Multigenerational Family with Childhood Apraxia of Speech. (24th November 2016) - Carrigg, Bronwyn; Parry, Louise; Baker, Elise; Shriberg, Lawrence D.; Ballard, Kirrie J.
Abstract: Objective: This study describes the phenotype in a large family with a strong, multigenerational history of severe speech sound disorder (SSD) persisting into adolescence and adulthood in approximately half the cases. Aims were to determine whether a core phenotype, broader than speech, separated persistent from resolved SSD cases; and to ascertain the uniqueness of the phenotype relative to published cases. Method: Eleven members of the PM family (9–55 years) were assessed across cognitive, language, literacy, speech, phonological processing, numeracy, and motor domains. Between group comparisons were made using the Mann–Whitney U -test ( p < 0.01). Participant performances were compared to normative data using standardized tests and to the limited published data on persistent SSD phenotypes. Results: Significant group differences were evident on multiple speech, language, literacy, phonological processing, and verbal intellect measures without any overlapping scores. Persistent cases performed within the impaired range on multiple measures. Phonological memory impairment and subtle literacy weakness were present in resolved SSD cases. Conclusion: A core phenotype distinguished persistent from resolved SSD cases that was characterized by a multiple verbal trait disorder, including Childhood Apraxia of Speech. Several phenotypic differences differentiated the persistent SSD phenotype in the PM family from the few previously reported studies of large families with SSD, including the absence of comorbid dysarthria and marked orofacial apraxia. This study highlights how comprehensive phenotyping can advance the behavioral study of disorders, in addition to forming a solid basis for future genetic and neural studies.